2013
DOI: 10.1038/nchembio.1277
|View full text |Cite
|
Sign up to set email alerts
|

Antituberculosis thiophenes define a requirement for Pks13 in mycolic acid biosynthesis

Abstract: We report a new class of thiophene (TP) compounds that kill Mycobacterium tuberculosis (Mtb) by the novel mechanism of Pks13 inhibition. An F79S mutation near the catalytic Ser-55 site in Pks13 conferred TP-resistance in Mtb. Over-expression of wild-type pks13 resulted in TP-resistance and over-expression of the F79S pks13 mutant conferred high-level resistance. In vitro, TP inhibited fatty acyl-AMP loading onto Pks13. TP inhibited mycolic acid biosynthesis in wild-type Mtb, but to a much lesser extent in TP-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
149
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 57 publications
1
149
0
1
Order By: Relevance
“…The return of interest in whole cell -based screening that the TB field has witnessed in recent years has led to the identification of thiophenes and other compounds active against Pks13 Wilson et al 2013), diaryl coumarin -based compounds active against FadD32 (Stanley et al 2013), and diverse chemotypes active against the TMM transporter, MmpL3 (Grzegorzewicz et al 2012a;Stanley et al 2012;Ioerger et al 2013;Remuinan et al 2013). BM212 and derivatives (La Poce et al 2013) and SQ109, a drug candidate originally designed to be an EMB analog and currently undergoing phase II clinical trials (Sacksteder et al 2012;Tahlan et al 2012), were also shown to kill Mtb through the inhibition of MmpL3.…”
Section: Mtb Lipidsmentioning
confidence: 99%
“…The return of interest in whole cell -based screening that the TB field has witnessed in recent years has led to the identification of thiophenes and other compounds active against Pks13 Wilson et al 2013), diaryl coumarin -based compounds active against FadD32 (Stanley et al 2013), and diverse chemotypes active against the TMM transporter, MmpL3 (Grzegorzewicz et al 2012a;Stanley et al 2012;Ioerger et al 2013;Remuinan et al 2013). BM212 and derivatives (La Poce et al 2013) and SQ109, a drug candidate originally designed to be an EMB analog and currently undergoing phase II clinical trials (Sacksteder et al 2012;Tahlan et al 2012), were also shown to kill Mtb through the inhibition of MmpL3.…”
Section: Mtb Lipidsmentioning
confidence: 99%
“…Além disso, esse composto exibiu ação bactericida e sua combinação com isoniazida resultou em efeito esterilizante. 62 De maneira similar, foram descritos derivados de 2-aminotiofenos com potente atividade antituberculose, possuindo como alvo a enzima Pks13. Especificamente, o composto 15 (Figura 5) apresentou CIM 90 de 0,69 μmol L -1 em MTB H 37 Rv.…”
Section: Alvos Envolvidos Com a Biossíntese Da Parede Celularunclassified
“…Pks13 then uses its thioesterase activity to release these nascent mycolates and transfers them to trehalose thereby forming the trehalose monomycolate precursor [53]. Several groups have independently found thiophene and benzofuran compounds [26,41,42] that target Pks13, thus ablating mycolic acid synthesis [43]. Ioerger et al discovered a benzofuran that seemingly inhibits the thioesterase activity (residues 1400-1700) as resistance mutations (D1644G and D1607N) mapped there [26].…”
Section: (Iv) Pks13mentioning
confidence: 99%